2008
DOI: 10.1002/jcp.21481
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells modulate the differentiation of bone marrow mesenchymal stem cells into hepatocyte‐like cells

Abstract: Differentiation of stem cells is tightly regulated by the microenvironment which is mainly composed of nonparenchymal cells. Herein, we investigated effect of hepatic stellate cells (HSCs) in different states on mesenchymal stem cells (MSCs) differentiation. Rat HSCs were isolated and stayed quiescent within 5 days. Primary HSCs were activated by being in vitro cultured for 7 days or cocultured with Kupffer cells for 5 days. MSCs were cocultured with HSCs of different states. Expression of hepatic lineage mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Deng et al 242 have analyzed the effect of co-culturing Kupffer cells and activated HeSCs with MSCs. They found that activated HeSCs in the presence of Kupffer cells express significant levels of HGF and induce differentiation of MSCs into hepatocyte-like cells that are able to produce glycogen deposition.…”
Section: Msc Signaling Mechanisms In Liver Fibrosismentioning
confidence: 99%
“…Deng et al 242 have analyzed the effect of co-culturing Kupffer cells and activated HeSCs with MSCs. They found that activated HeSCs in the presence of Kupffer cells express significant levels of HGF and induce differentiation of MSCs into hepatocyte-like cells that are able to produce glycogen deposition.…”
Section: Msc Signaling Mechanisms In Liver Fibrosismentioning
confidence: 99%
“…It is generally believed that under the microenvironment of fibrosis or cirrhosis most transplanted stem cells differentiate into hepatocytes, and hepatic stellate cells by hepatic stellate cells [24] [54]. However, in a mouse model of liver fibrosis or cirrhosis with remarkable inflammation [23], the majority of injected stem cells differentiated into myofibroblasts, resulting in liver fibrosis being aggravated.…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%
“…Secreting factors derived from these cells are assumed to induce hepatic differentiation [54]. Deng et al observed the hepatocyte-like cells after co-culture rat BM-MSCs with activated HSC.…”
Section: Induction By Soluble Growth Factors or Cytokines-defined Mediummentioning
confidence: 99%